Voting Patterns in Post-Mubarak Egypt - Martini, Jeffrey (RAND Corporation, 2013)
To help U.S. policymakers and Middle East watchers better understand voting patterns in Egypt, RAND researchers identified regional voting trends and where Islamists are strongest. It appears they may face increasing challenges.